Modern Dressing Wound Care Mempercepat Proses Penyembuhan Ulkus Kaki pada Pasien Diabetes: A Systematic Review - Bangu Bangu; Heriviyatno Julika Siagian; Rosani Naim; Evodius Nasus (Jurnal Surya Medika (JSM), 2021)
Foot ulcers in diabetic patients should receive treatment to reduce the risk of infection and amputation and improve function and quality of life. Wound care techniques are developing very quickly, which can help nurses and patients to improve the healing of foot ulcers in diabetic patients. Several wound care methods that can accelerate the healing process of foot ulcers in DM patients include modern wound dressings, the process of healing diabetic ulcers. With modern dressing methods, chronic wound care with modern dressings, the potential of green tea in wound healing, honey as a debridement agent. Objective: This study reviews several dressing methods that accelerate the healing process of foot ulcers in diabetic patients. This study uses a Systematic Review based on Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) to identify all published literature using relevant databases and keywords. In the 5 articles that we analyzed, the use of modern wound dressings proved to be more effective in accelerating wound healing, especially foot ulcers in diabetic patients. Modern wound care (Modern wound dressing), chronic wound care with modern dressings, the potential of green tea in wound healing, Honey as a debridement agent: a systematic review. And the role of the family in helping patients take medication regularly is the right choice to accelerate the healing process of foot ulcers in diabetic patients with more cost-effective treatment.